Gene Amplification and Overexpression of CDK4 in Sporadic Breast Carcinomas Is Associated with High Tumor Cell Proliferation - An, Han-Xiang (American Society for Investigative Pathology, 1999)
Amplification of the cyclin-dependent kinase 4 (CDK4) gene, located at 12q13-q14, has been found as an alternative genetic alteration to CDKN2A inactivation in various human tumors including malignant gliomas and sarcomas. In the present study, we have evaluated the frequency of the CDK4 gene amplification in sporadic breast cancer by applying a nonradioactive quantitative differential polymerase chain reaction based on fluorescent DNA technology. Fluorescent-labeled polymerase chain reaction products were analyzed with an automated DNA sequencer. Amplification of CDK4 gene was detected in 15 (15.8%) of 95 breast cancers. All tumors with CDK4 gene amplification showed high CDK4 protein expression determined by immunohistochemistry. Furthermore, the mean Ki-67 labeling index in tumors with CDK4 gene amplification was significantly higher than in those without CDK4 gene amplification. No significant associations were observed between CDK4 gene amplification and any specific histopathological parameter. The findings of this study provide the first evidence of CDK4 gene amplification in breast cancer and suggest that CDK4 gene amplification appears to be of importance in the pathogenesis of a subset of sporadic breast cancer.